Sleep health - National Sleep Foundation (Elsevier Inc, 2015)
Sleep Health Journal of the National Sleep Foundation is a new, multidisciplinary journal that explores sleep's role in population health and elucidates the social science perspective on sleep and health. Aligned with the National Sleep Foundation's global authoritative, evidence-based voice for sleep health, the journal serves as the foremost publication for manuscripts that advance the sleep health of all members of society. The scope of the journal extends across diverse sleep-related fields, including anthropology, education, health services research, human development, international health, law, mental health, nursing, nutrition, psychology, public health, public policy, fatigue management, transportation, social work, and sociology--Publisher's website.
Keywords: Sleep : Periodicals; Sleep; Public Health - General